Progress on the biological characteristics and physiological activities of fucoxanthin produced by marine microalgae - Gong, Bing; Ma, Silu; Yan, Yajun; Wang, Zhaokai (Frontiers in Marine Science, 2024)
Background Fucoxanthin is a carotenoid found in seaweed. Its unique chemical structure gives it a variety of properties. Thus fucoxanthin have attracted the attention of companies and researchers. Methods Scientific papers were collected from the database. Duplicates and unavailable literature were excluded first. Then the remaining literature was categorized for referencing in the review. Results This article contains a summary of the microalgae species producing fucoxanthin and their progress in breeding and cultivation modes. Additionally, the review summarized the progress of research on physiological activities and organized the experimental models used in these studies. Conclusions These present findings may provide information for the upstream production of fucoxanthin from algal species selection to process optimization. The analysis of the physiological activity results will help advance subsequent physiological and biochemical experiments. Furthermore, it intends to pique researchers’ enthusiasm for fucoxanthin and enrich related research data to accelerate the development of this natural product.